Review of Husband's Polygamy Permit (Study of Rantauprapat Religious Court Decision Number 778/Pdt.G/2021/Pa.Rap) - Julia Asmini; Toni Toni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Polygamy is a form of legal marriage if the terms and conditions are fulfilled in accordance with the laws and regulations. Where basically Islam allows for husbands to remarry (polygamy) as long as they can be fair. The Religious Courts Council has absolute absolute authority to examine, hear and decide every case. In consideration of deciding the case for a polygamy permit, the judge refers to the rules of the Qur'an, Hadith of the Prophet, Law No. 1 of 1974 amended Law No. 16 of 2019 concerning Marriage, Compilation of Islamic Law and legislation that can be used as a basis for deciding cases. As for the typeThis research is based on normative law research by way of a case study of the decision of the Rantauprapat Religious Court Number. 778/Pdt.G/2021/PA.Rap. This type of qualitative research is descriptive in which the research is to provide a detailed, clear and systematic description. Basis for consideration of the Panel of Judges in deciding the Polygamy permit in Case Number. 778/Pdt.G/2021/PA.RAP.Article 4 Paragraph (2) Explains "The court referred to in paragraph (1) of this article only gives permission to a husband who will have more than one wife if: a. the wife cannot carry out her obligations as a wife, b. the wife has a disability or an incurable disease, c. the wife cannot give birth to offspring”, and Article 5 Paragraph (1). In the Compilation of Islamic Law, Article 57 and Article 58 Paragraph (1). From the conclusion that the Judge of the Rantauprapat Religious Court in deciding it was in accordance with the legal basis in writing as the basis for adjudicating.